2011
DOI: 10.1158/0008-5472.can-11-1773
|View full text |Cite
|
Sign up to set email alerts
|

Asialoglycoprotein Receptor Promotes Cancer Metastasis by Activating the EGFR–ERK Pathway

Abstract: Although the importance of glycans in malignant cell behavior is well documented, the potential involvement of endogenous lectins as modifiers of progression and metastasis in the tumor microenvironment has not been explored. In this study, we show that loss of the hepatic asialoglycoprotein receptor (ASGPR) in mice severely reduces the frequency of spontaneous lung metastasis after intrahepatic implantation of murine Lewis lung carcinoma (3LL) cells. Conversely, in vitro treatment with recombinant ASGPR incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…16 Recent research documented that ASGR1 activates the epidermal growth factor receptor (EGFR)-ERK pathway and induces matrix metalloproteinase-9 (MMP-9) expression. 31 In the present study, we observed short-term phosphorylation of ERK1/2 within 30 min after TNF-α stimulation, which peaked at 15 min, consistent with previous findings. 8 Although galactose enhanced phosphorylation of ERK1/2 slightly at 30 min, we speculate that this effect is abated.…”
Section: Discussionsupporting
confidence: 93%
“…16 Recent research documented that ASGR1 activates the epidermal growth factor receptor (EGFR)-ERK pathway and induces matrix metalloproteinase-9 (MMP-9) expression. 31 In the present study, we observed short-term phosphorylation of ERK1/2 within 30 min after TNF-α stimulation, which peaked at 15 min, consistent with previous findings. 8 Although galactose enhanced phosphorylation of ERK1/2 slightly at 30 min, we speculate that this effect is abated.…”
Section: Discussionsupporting
confidence: 93%
“…The process of cancer cell metastasis was associated with the activation of EGFR signal transduction pathways 45,46…”
Section: Discussionmentioning
confidence: 99%
“…After stimulation by cytokines, growth factors, or other exogenous activators, MMP9 expression is upregulated mostly at the transcriptional level (53,67,72). MMP9 transcription is also induced by several oncogenic viruses, such as EBV, Kaposi's sarcomaassociated herpesvirus, human papillomavirus 16, and hepatitis B virus (14,43,70,73).…”
Section: Discussionmentioning
confidence: 99%